Assessment of causal associations between handgrip strength and cardiovascular diseases: A two sample mendelian randomization study - Zhuo, Chengui; Zhao, Jianqiang; Wang, Qiqi; Lin, Zujin; Cai, Haipeng; Pan, Huili; Chen, Lei; Jin, Xiangyu; Jin, Hong; Xu, Longwei; Tao, Xiyan (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Several observational studies have identified that handgrip strength was inversely associated with cardiovascular diseases (CVDs). Nevertheless, causality remains controversial. We conducted Mendelian randomization (MR) analysis to examine whether handgrip strength and risk of CVDs are causally associated. Methods: We identified 160 independent single nucleotide polymorphisms (SNPs) for right-hand grip strength and 136 independent SNPs for left-hand grip strength at the genome-wide significant threshold (P < 5x10-8) from UK Biobank participants and evaluated these in relation to risk of CVDs. MR estimates was calculated using the inverse-variance weighted (IVW) method and multiple sensitivity analysis was further conducted. Results: Genetical liability to handgrip strength was significantly associated with coronary artery disease (CAD) and myocardial infarction (MI), but not stroke, hypertension, or heart failure. Additionally, there was significant association between right-hand grip strength and atrial fibrillation (OR, 0.967; 95% CI, 0.950-0.984; p= 0.000222), however, suggestive significance was found between left-hand grip strength and atrial fibrillation (OR, 0.977; 95% CI,0.957-0.998; p = 0.033). Results were similar in several sensitivity analysis. Conclusion: Our study provides support at the genetic level that handgrip strength is negatively associated with the risk of CAD, MI, and atrial fibrillation. Specific handgrip strength interventions on CVDs warrant exploration as potential CVDs prevention measures.